KORELASI ANTARA ACADEMIC SELF EFFICACY DENGAN NILAI UJIAN SOCA BLOK 1.3 MAHASISWA JURUSAN KEDOKTERAN UMUM FAKULTAS KEDOKTERAN UNIVERSITAS JENDERAL SOEDIRMAN - Heidy Angelina Mulyadi; Catharina Widiartini; Muhammad Zaenuri Syamsu Hidayat (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Introduction : Academic self efficacy (ASE) is student's self confidence on his/her ability to be succeed in the assignments and to organize learning activities in order to achieve the expected achievement. A high ASE helps students overcome anxiety in facing exams. One form of the final block exam at the General Medicine Department, Faculty of Medicine Universitas Jenderal Soedirman (KU, FK Unsoed) that often causes anxiety is the Structured Oral Case Analysis (SOCA). Objective : To find out whether there was a correlation between ASE and Block 1.3 SOCA test scores. Methods : This was an observational analytic study using a cross sectional design. The respondents were student participants of Block 1.3 General Medicine Department, Faculty of Medicine Universitas Jenderal Soedirman batch 2021 determined by total sampling method based on the inclusion and exclusion criteria. ASE score were collected using the Indonesian version of MSLQ questionnaire, self efficacy for learning and performance subscale. The correlation between ASE scores and pre-remedial SOCA test scores was analyzed using Pearson test with significance level at p<0,05. Results : Data obtained from 126 students (response rate 100%). Most (47,6%) students had high ASE level. The biggest (62,7%) proportion of the SOCA test scores was at level E. The results of the Pearson test showed that the value of p=0,020 and r=0,826. Conclusion : There is a significant correlation with a positive direction and the strength of the correlation is very strong between ASE and SOCA test scores of student participants of Blok 1.3 General Medicine Department, Faculty of Medicine Universitas Jenderal Soedirman.